OPTIMIZATION OF THE ACEH BEEF CATTLE PRODUCTION AND PROCESS USING SWOT ANALYSIS AND INDUSTRIAL SUPPLY CHAIN APPROACHES - Khairol Mizan Us; M. Aman Yaman; Edy Fradinata (Universitas Syiah Kuala, 2021)
The problem in management process and production of Aceh beef cattle farms in Aceh Besar has not been explored. This study aimed to determine the basic system of supply chain for the Aceh beef cattle production in Central Aceh Besar developed a model for optimizing the supply chain management and sustainability to increase productivity and business efficiency. This research used SWOT analysis and industrial supply chain approaches. The results showed that the current supply chain system of the Aceh beef cattle industry in Aceh Besar which has been running so far, needs to be strengthened to increase production and population of Aceh beef cattle in the future. There were 4 issues were identified: time, 29.6% faster than the current supply chain supply time; method, 60% no longer needed a business intermediary; cost, 21.4% of the live weight price of cattle was cheaper than the live weight price of current supply chain cattle; and stages, 30.8% shorter than the ongoing supply chain stages. The result of the SWOT analysis matrix showed that the SO (strength-opportunities) strategy was the main strategy for business developing of Aceh beef cattle in Central Aceh. In conclusion, it is necessary to optimize the implementation of the supply chain of Aceh Cattle Industry at Central Aceh by utilizing its strengths and suppressing the existing weaknesses from the breeding production to marketing process.